2019
DOI: 10.1016/j.healthplace.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Perceived neighborhood social cohesion moderates the relationship between neighborhood structural disadvantage and adolescent depressive symptoms

Abstract: There is a dearth of research exploring the moderating role of the social environment on neighborhood structural disadvantage and depressive symptoms, particularly among adolescents. Therefore, we examined if adolescent perceptions of neighborhood social cohesion and safety moderated the association between neighborhood structural disadvantage and adolescent depressive symptoms. This cross-sectional study used data from the National Longitudinal Study of Adolescent to Adult Health (Add Health). The study sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 49 publications
3
37
0
1
Order By: Relevance
“…Our findings are consistent with previous research linking neighborhood disadvantage to accelerated DNAm aging in children and adults (22,27). In our study, we found that women's DNAm aging was more sensitive to neighborhood poverty and Neighborhood social cohesion has also been shown to affect physical and mental health outcomes and may have effects at the molecular levels (16,(30)(31)(32)(33). In a study of 1,226 adults in the Multi-Ethnic Study of Atherosclerosis (MESA), the neighborhood social environment, measured as a summary score that included social cohesion, was associated with DNAm in stress-and inflammation-related genes (16).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with previous research linking neighborhood disadvantage to accelerated DNAm aging in children and adults (22,27). In our study, we found that women's DNAm aging was more sensitive to neighborhood poverty and Neighborhood social cohesion has also been shown to affect physical and mental health outcomes and may have effects at the molecular levels (16,(30)(31)(32)(33). In a study of 1,226 adults in the Multi-Ethnic Study of Atherosclerosis (MESA), the neighborhood social environment, measured as a summary score that included social cohesion, was associated with DNAm in stress-and inflammation-related genes (16).…”
Section: Discussionsupporting
confidence: 92%
“…Positive aspects of the neighborhood, such as perception of neighborhood social cohesion, may act to buffer the effects of an adverse neighborhood environment on DNAm aging, as found in studies relating neighborhoods to health (30)(31)(32)(33). Accordingly, our study sought to investigate both the independent and joint impacts of neighborhood quality and social cohesion on three measures of DNAm aging-Horvath's epigenetic clock, Hannum's epigenetic clock, and Levine's PhenoAge-among a sample of predominately Black adults living in Detroit, MI (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Much scholarship over the past two decades emphasizes the consequentiality of neighborhoods for their residents' physical, mental, and social well-being (e.g., Blair et al, 2014;Dawson et al, 2019;Kim & Ross, 2009;Matheson et al, 2006;Van Eijk, 2010). In particular, neighborhood social cohesion, trust, and support are important influences upon health and quality of life (Cramm et al, 2013;Feldman & Oberlink, 2003;Putnam, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, neighborhood social cohesion, trust, and support are important influences upon health and quality of life (Cramm et al, 2013;Feldman & Oberlink, 2003;Putnam, 2001). Dawson et al (2019), for example, show through cross-sectional analyses the significant and complex relationships between adolescents' depressive symptoms and neighborhood structural disadvantage, safety, and social cohesion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation